Pengaruh model problem based learning (PBL) berbantuan media animasi terhadap hasil belajar fisika peserta didik pada materi termodinamika dan gelombang mekanik di kelas XI MAN 2 Padang - Bizar al furqan; Ratnawulan Ratnawulan (PILLAR OF PHYSICS EDUCATION, 2019)
This study aims to determine the effect of problem-based learning models with the help of animation media on student learning outcomes on thermodynamic material and mechanical waves in class XI MAN 2 PADANG. The method used in this experiment is to use quasy experiments with random control group designs. The population in this study were students of class XI MAN 2 PADANG who were registered in the even semester 2018/2019. Sampling is done by purposive sampling technique whose research results are concentrated in cognitive and psycomotor values only. After conducting this research it can be concluded that problem-based learning with the help of animation media has a good influence on student learning outcomes.